Remoção de óleo da água de produção por flotação em coluna utilizando tensoativos de origem vegetal - Silva, Paula Katherine Leonez da (2008)
In the petroleum industry, water is always present in the reservoir formation together with petroleum and natural gas and this fact provokes the production of water with petroleum, resulting in a great environmental impact. Several methods can be applied for treatment of oily waters, such as: gravitational vases, granulated media filtration systems, flotation process, centrifugation process and the use of hydrocyclones, which can also be used in a combined way. However, the flotation process has showed a great efficiency as compared with other methods, because these methods do not remove great part of the emulsified oil. In this work was investigated the use of surfactants derived from vegetable oils, OSS and OGS, as collectors, using the flotation process in a glass column with a porous plate filter in its base for the input of the gaseous steam. For this purpose, oil/water emulsions were prepared using mechanical stirring, with concentrations around 300 ppm. The air flow rate was set at 700 cm3/min and the porous plate filter used for the generation of the air bubbles has pore size varying from 16 to 40 Pm. The column operated at constant volume (1500mL). A new methodology has been developed to collect the samples, where, instead of collecting the water phase, it was collected the oil phase removed by the process in the top of the flotation column. It has been observed that it is necessary to find an optimum surfactant concentration to achieve enhanced removal efficiency. Being for OSS 1.275 mmol/L and for OGS 0.840 mmol/L, with removal efficiencies of 93% and 99%, respectively, using synthetic solutions. For the produced water, the removal in these concentrations was 75% for OSS and 65% for OGS. It is possible to remove oil from water in a flotation process using surfactants of high HLB, fact that is against the own definition of HLB (Hydrophile-Lipophile Balance). The interfacial tension is an important factor in the oil removal process using a flotation process, because it has direct interference in the coalescence of the oil drops. The spreading of the oil of the air bubble should be considered in the process, and for the optimum surfactant concentrations it reached a maximum value. The removal kinetics for the flotation process using surfactants in the optimum concentration has been adjusted according to a first order model, for synthetic water as for the produced water.